Implementation of Punishment to Reduce Tantrum Behavior in Children with Cerebral Palsy - Amani, Risca; Rahmahtrisilvia, Rahmahtrisilvia; Maulidazani, Fitri (CV. Lentera Literasi Indonesia, 2025)
Cerebral palsy children have behavioral problems in the form of tantrums. If this tantrum behavior is left unchecked, it will have a negative impact on the child's development and learning process. One of the behavior modification techniques that can be applied to reduce tantrum behavior is punishment. This study aims to see the impact of punishment in reducing tantrum behavior. The research method used is a case study to see the decline in tantrum behavior in cerebral palsy. Data were collected through observation and documentation in the form of recording tantrum behavior in terms of duration and frequency. The results showed that the consistent application of punishment can reduce the frequency of tantrums in children with cerebral palsy from Cycle 1 to Cycle 2. Cycle 1 tantrum behavior appeared four times with a duration of 35 minutes, while in Cycle 2, tantrum behavior appeared twice with a duration of 20 minutes. This shows how important it is to use a scientific approach to manage behavior. Appropriate behavior-based interventions can improve children's social and academic skills and reduce maladaptive behaviors.